(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
An analysis of Hermeneutics and of the different phases through which is haspassed, from Humanism to the ontological, then transposing this journey to the fieldof legal reflection: from Hermeneutics as a technique of interpretation to the Philosophyof Law as Hermeneutic.